Legal Liability Towards The Abuse Of Doctor's Authority In Performing Visum Et Repertum - Yusanuli; Fauzul Romansah; Rifka Yudhi (Fakultas Hukum Universitas Lampung, 2021)
Visum et Repertum (VeR) is in the form of a written statement made by doctors who have to take an oath of office, based on things seen and discovered upon examination of the dead or wounded allegedly caused by a criminal act. KUHAP does not mention the term visum et repertum, but KUHAP is one of the legal bases in making VeR. VeR is not only needed in criminal case examination but also civil cases in some instances. The exact cause of a person's death can be related to events in criminal law as well as civil law as in the claim insurance or determination of heirs related to the distribution of inheritance rights. Given the urgency of VeR as one of the evidence used before court proceedings, in making VeR, there is a potential for abuse of power by doctors by making VeR not based on actual examination results. Such abuse of authority by doctors has violated the moral and ethical aspects which override the values of truth and justice. Therefore, the problems in this article focus on what is the authority of doctors in administering Visum et Repertum and what is the legal responsibility for the abuse of doctor's authority in making Visum et Repertum. The results of the discussion indicated that: doctors have the authority to, among others: accept victims sent by investigators; request a letter requesting a statement of VeR; a specialist can only carry out medical examination of the victim; signing of the VeR statement following the applicable laws and regulations, and delivery of completed evidence may only be submitted to the investigator accompanied by an official report. Making VeR unlawfully is not clearly explained in the Criminal Procedure Code. However, the use of VeR against the law occurs when VeR becomes an instrument of action against the law as formulated in the norms of every criminal act. Therefore, it is a form of legal responsibility for doctors who abuse their authority regarding VeR can be pursued through 4 (four) types of sanctions, including administrative sanctions, civil sanctions, criminal sanctions, and medical discipline sanctions.